Analyzing, Designing and Developing Arabic Conversation Material Based on Communicative Approach for Undergraduate AFL Learners - Zubair, K. M. A. Ahamed (RADINKA JAYA UTAMA PUBLISHER, 2024)
The landscape of Arabic language education has evolved significantly, with a growing emphasis on enhancing students' oral communication skills. This study focuses on developing supplementary conversational Arabic materials to support undergraduate students enrolled in the B.A. The Arabic program at New College, Chennai, is affiliated with the University of Madras, India. The aim is to address the gap in existing materials by adopting a communicative approach, emphasizing practical language use in everyday contexts. This research aims to produce and evaluate conversational Arabic materials that facilitate an enjoyable and effective learning experience for undergraduate Arabic language learners. Specifically, the objectives include developing thematic conversations aligned with student needs, enhancing oral proficiency through interactive exercises, and validating the suitability of the materials in a classroom setting. Following the Dick and Carey instructional design model, the development process involved several iterative stages: identifying learning objectives, conducting instructional and learner analyses, formulating content, designing interactive exercises, and evaluating the materials through expert reviews and field testing. Data collection methods included expert evaluations, student feedback, and quantitative assessments to ensure the effectiveness and appropriateness of the developed materials. The developed conversational Arabic materials were positively evaluated across multiple dimensions. Content and instructional design experts rated the materials highly for clarity, relevance, and engagement. Student feedback indicated significant improvement in oral communication skills, with a majority expressing satisfaction and increased confidence in using Arabic in everyday interactions.